A History of What Comes Next - Neuvel, Sylvain (Dublin Michael Josph, 2021)
"Always run, never fight. Preserve the knowledge. Survive at all cost. Take them to the stars. Over 99 identical generations, Mia's family has shaped human history to push them to the stars, making brutal, wrenching choices and sacrificing countless lives. Her turn comes at the dawn of the age of rocketry. Her mission: to lure Wernher Von Braun away from the Nazi party and into the American rocket program, and secure the future of the space race. But Mia's family is not the only group pushing the levers of history: an even more ruthless enemy lurks behind the scenes. A darkly satirical first contact thriller, as seen through the eyes of the women who make progress possible and the men who are determined to stop them."--Provided by publisher.